The Development of the Hiring Process in Iceland - Tinni Kári Jóhannesson 1987- (2017)
This study is aimed to discuss and explore the development of the hiring process in Iceland over the past twenty years. Previously, studies on the topic have been quantitative and therefore lacking insight, as well as reasons, for the development that was taking place. Other Master studies completed in Iceland have been mostly referenced with global research and theories. The development of the hiring process globally has increased professionalism and created multiple methods in selecting and acquiring talent. Human Resources (HR) professionals have been hiring candidates long before twenty years ago. However, since the interviewees for this study had experience that covered this period, the focus of this thesis took aim to a like timeframe. The individuals that were interviewed for this study experienced similar global development trends. Furthermore, it was concluded that professionalism and multiple methods towards assessing candidates and acquiring talented individuals were the greatest areas of innovation. The methodology in this study was qualitative and was executed by conducting ten interviews with HR professionals that had been involved with the hiring function of HR for over five years. Results show that the Icelandic HR industry and therefore, hiring function, is on the second and third maturity stage. Participants had similar experiences as the quantitative reports of The Cranet Report in Iceland. The trends are highly influenced by global trends and economical fluctuation. Most development in the hiring process is due to demands and the needs of Icelandic organizations. Measurement of the outcomes of the hiring process were one of the findings that seem to highly lacking. Assessment and measurement tools are one of the aspects that would need to change for Icelandic organizations to reach the fourth maturity stage of HR practices.